STRATEGI PEMASARAN PRODUK TABUNGAN EMAS DI PT. PEGADAIAN (PERSERO) CABANG NGANJUK - Yeti Sinta Dewi; Achmad Syaichu; Agustin Sukarsono (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2020)
Marketing is one of the most important keys in the business world. Marketing goods or services is an activity of offering or selling but more broadly than that, a company is said to be successful in terms of how the company is able to overcome the constraints of the company's internal and external factors. This study aims to determine the marketing strategy of the Gold Savings product in PT. PEGAGAIAN (Persero) Nganjuk Branch. The analysis used in this study is a SWOT analysis in which there are internal and external factors in the company. This type of research is field research (field research) using descriptive research methods with a qualitative approach. Based on the results of the IFE matrix 2.98 and EFE 2.98, it illustrates that the company is in an average internal condition and the business response to external factors is high, while for the IE matrix the company occupies the V quadrant, namely the strategy to maintain and maintain (hold and maintain) strategies that can be applied are market penetration strategies and product development, the results of the QSPM matrix of product development (product development) with a total TAS of 6.63, while other alternatives have lower market penetration (product development). with a total TAS of 5.94. So that the best alternative strategies that can be applied to these companies are market penetration and product development strategies.